Personal Branding “GEMOY” Prabowo Subianto on “Presidential Election 2024” in TikTok Media Sosial - Fahruz Fahruz; Alvine Septian Nugraha Septian Nugraha; Farida Nurfalah (Rescollacom (Research Collaborations Community), 2025)
Personal Branding “gemoy” is one of the branding shown by one of the political parties in Indonesia, namely the Gerindra party on candidate Prabowo Subianto. This branding is intended to attract the interest of Gen Z as the largest voter in the 2024 Presidential Election. This study aims to determine how the use of Personal Branding “Gemoy” on Gerindra's TikTok social media for Gen Z people. The research method used in this study uses a qualitative approach and tests the validity of the data using source triangulation. Using data analysis includes data display, reduction, and conclusions. Informant selection technique through followers of Gerindra's TikTok account using a sampling proposal of 5 informants. The results obtained from in-depth research regarding the Social Identity point of view are used to examine the data obtained. That the “gemoy” branding published on social media TikTok Gerindra can attract and be accepted by Gen Z circles. In 3 indicators (categorization, identification, comparison) have results that tend to be the same, that this branding is a branding that is not suitable for branding, but this branding can be accepted by them due to the results of the 2024 presidential election victory which in numbers is quite dominant.